Characterization of a C9orf72 Knockout Danio rerio model for ALS and cross-species validation of potential therapeutics screened in Caenorhabditis elegans - Alexandre Emond; Carl Laflamme; Martine Therrien; Meijiang Liao; Claudia Maios; Audrey Labarre; Pierre Drapeau; J. Alex Parker (PLoS ONE, 2026)
Intronic hexanucleotide repeat expansions in the C9orf72 gene represent the most common genetic cause of the neurodegenerative diseases amyotrophic lateral sclerosis (ALS) and frontotemporal dementia. This expansion decreases C9orf72 expression in affected patients, indicating that loss of C9orf72 function (LOF) acts as a pathogenic mechanism. Several models using Danio rerio (zebrafish) for C9orf72 depletion have been developed to explore disease mechanisms and the consequences of C9orf72 LOF. However, inconsistencies exist in reported phenotypes, and many have yet to be validated in stable germline ablation models. To address this, we created a zebrafish C9orf72 knockout model using CRISPR/Cas9. The C9orf72 LOF model demonstrates, in a generally dose-dependent manner, increased larval mortality, persistent growth reduction, and motor deficits. Additionally, homozygous C9orf72 LOF larvae exhibited mild overbranching of spinal motoneurons. To identify potential therapeutic compounds, we performed a screen on an established Caenorhabditis elegans ( C. elegans ) C9orf72 homologue ( alfa-1 ) LOF model, identifying 12 compounds that enhanced motility, reduced neurodegeneration, and alleviated paralysis phenotypes. Motivated by the shared motor phenotype, 2 of those compounds were tested in our zebrafish C9orf72 LOF model. Pizotifen malate was found to significantly improve motor deficits in C9orf72 LOF zebrafish larvae. We introduce a novel zebrafish C9orf72 knockout model that exhibits phenotypic differences from depletion models, providing a valuable tool for in vivo C9orf72 research and ALS therapeutic validation. Furthermore, we identify pizotifen malate as a promising compound for further preclinical evaluation.